Pemanfaatan Arang Aktif Cangkang Kelapa Sawit Teraktivasi H3PO4 untuk Penurunan Kadar Besi (Fe), Mangan (Mn) dan Kondisi pH pada Air Asam Tambang - Hanna Najmia; Emmy Sri Mahreda; Rizqi Putri Mahyudin; Kissinger Kissinger (Universitas Lambung Mangkurat, 2021)
Acid mine drainage is water containing dissolved metals such as iron (Fe), manganese (Mn), and other sulfate compounds. It causes various impacts such as environmental pollution, reducing soil fertility, disrupting the health of surrounding communities, and causes the corrosion of mining equipment. The adsorption method is used to reduce the concentration of heavy metals from liquid waste. Activated carbon of palm shell can be used as a heavy metal adsorbent in acid mine drainage. The research aims to determine the utilization of activated palm shell activated H3PO4for decreased levels of Fe, Mn and pH conditions in acid mine drainage. The research methods consist of carbonation process, activation, activated carbon characteristic test, Scanning Electron Microscope (SEM) test, activated carbon adsorption test of palm shell to Fe, Mn and pH condition in acid mine drainage. It used a Complete Randomized Design (RAL) with one factor. The data analyzed with ANOVA and Duncan test. The result showed that activated carbon of palm shell activated H3PO4 meets the quality of active carbon characteristics in accordance with SNI 06-3730-95, the active carbon of palm shells with H3PO4 activation has a significant effect on changes in the condition of heavy metals Fe and Mn, also the pH of acid mine drainage. The result showed that the most effective H3PO4 activated carbon dose variation on the Fe parameter is 30g, the Mn parameter is 20g and the pH is 30g.